2020
DOI: 10.1186/s12934-020-01304-5
|View full text |Cite
|
Sign up to set email alerts
|

Co-expressing GroEL–GroES, Ssa1–Sis1 and Bip–PDI chaperones for enhanced intracellular production and partial-wall breaking improved stability of porcine growth hormone

Abstract: Porcine growth hormone (pGH) is a class of peptide hormones secreted from the pituitary gland, which can significantly improve growth and feed utilization of pigs. However, it is unstable and volatile in vitro. It needs to be encapsulated in liposomes when feeding livestock, whose high cost greatly limits its application in pig industry. Therefore we attempted to express pGH as intracellular soluble protein in Pichia pastoris and feed these yeasts with partial wall-breaking for swine, which could release direc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…Fine examination of recombinant protein production revealed that chaperone co-expression, as an effective strategy for protein production, showed different effects on target proteins under different chaperone types and levels. For example, GroES-GroEL co-expression improved the expression level of porcine growth hormone (Deng et al, 2020) and the yield of the Fab antibody fragment (Levy et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Fine examination of recombinant protein production revealed that chaperone co-expression, as an effective strategy for protein production, showed different effects on target proteins under different chaperone types and levels. For example, GroES-GroEL co-expression improved the expression level of porcine growth hormone (Deng et al, 2020) and the yield of the Fab antibody fragment (Levy et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Addition of 10 mmol ascorbic acid to sorbitol/methanol co-feeding significantly increased the biomass of rhGH to 162.5 g/L (DCW) and total protein 1.14 g/L (Azadi et al, 2018). To express other GH from other species in the P. pastoris system (e.g., porcine, canine, Ailuropoda melanoleuca, and fish), codon optimized gene sequences are often used (Cho et al, 1987;Ascacio-Martínez & Barrera-Saldaña, 2004;Deng et al, 2020;Rothan et al, 2014). For example, porcine GH was produced more effectively in P. pastoris when using an optimized gene sequence, with expression levels reaching 10% of the total intracellular protein (Cho et al, 1987).…”
Section: Gh/gha Production In Other Species Such As Yeastmentioning
confidence: 99%
“…In comparison with the recently advancing attempts to phototrophically produce target proteins with microalgae, interestingly, the space-time yield (STY) utilizing yeasts is generally higher [ 58 , 59 , 60 ].…”
Section: Introductionmentioning
confidence: 99%